A PPP (PRESENTATION, PRACTICE, AND PRODUCTION) PHASE METHOD OF TEACHING SPEAKING TO UNIVERSITY STUDENTS - Yusuf, Adi (Educate, 2015)
Teaching speaking is considered as the â€œinteresting and challenging activityâ€. Indeed, it needs various ways in order to make students â€œactive in speakingâ€ during the class. This article would like to present the three phases, namely a PPP (Presentation, Practice, and Production) method in â€œteaching speaking to university studentsâ€. The fundamental principles of using this method is that the â€œstudents are smart and creativeâ€. Eventhough, they are considered as â€œintelligent and creativeâ€, teachers still need to guide or control them to anticipate any errors made by the students. Furthermore, it is important for teachers to know when to give â€œinstant correctionâ€ in class. When the class is focused on accuracy, teachers can give an â€œinstant correctionâ€. On the other hand, when it is focused on â€œfluencyâ€, it is not suggested that teachers give â€œinstant correctionâ€ and this may interfere with the goals of activity. Keywords: Presentation, Practice, Production, accuracy, fluency Abstrak Mengajar kelas speaking bisa dianggap sebagai aktivitas yang menarik dan menantang. Berbagai cara benar-benar perlu dilakukan untuk membuat para siswa aktif dalam berbicara selama pelajaran. Artikel ini membahas tentang tiga tahapan, yaitu sebuah metode PPP (Presentation, Practice, and Production) yang diterapkan dalam â€œmengajar speakingâ€ pada mahasiswa. Landasan dalam menggunakan metode ini adalah bahwa mahasiswa pandai dan kreatif. Meskipun, demikian pengajar masih perlu â€œmembimbing atau mengontrolâ€ mereka untuk mengantisipasi adanya kesalahan. Di samping itu, pengajar harus tahu kapan waktu yang tepat untuk memberikan â€œkoreksi langsungâ€ di kelas. Ketika kelas sedang difokuskan pada â€œketepatanâ€, pengajar bisa memberikan â€œkoreksi langsungâ€. Sebaliknya, ketika kelas sedang difokuskan pada â€œkepasihan/ kelancaranâ€, sebaiknya pengajar tidak memberikan â€œkoreksi langsungâ€ dan hal ini bisa mengganggu tujuan aktifitas kelas. Kata kunci: Presentation, Practice, Production, accuracy, fluency